Analisis Data Service Performance Broadband City Menggunakan Metode Grid 500 x 500 Meter - Najwa Khaerunisa (Jurnal Jaringan Telekomunikasi, 2018)
The stability of the services used by the users requires operators to provide good network quality to meet their needs. Broadband city performance conditions will affect the service, especially in data services used by users. Sometimes when a user uses a data service, there are disturbances that cause communication to be obstructed between users. The research objective is to determine the condition of the city broadband performance and the causes of the speed test measurement results are on indicators 1 and 2. Determination of performance using several parameters related to the measurement of service performance data on the 500x500 meter grid. The implementation of the 500x500 meter grid method is done by mapping the points of interest and the results of measuring service performance data to the 500x500 meter grid. The results of the measurement results of the RSRP and SINR drive test parameters have a percentage of 100% and 98.2%, speed test 96.19%, utility 92.6%. The measurement results at certain hours, drive test parameters RSRP and SINR have a percentage of 100% and 100%, speed test 100%. The measurement results of 10 grids with 4 different points in one grid, drive test parameters RSRP and SINR have a percentage of 100% and 100%, and 100% speed test. Locations that require network optimization are locations where the total speed test results are on indicators 1 and 2.